Design Education: A Trend in the Right Direction… - Souleles, Nicos; Clemente, Violeta; Börekçi, Naz A. G. Z. (My University, 2022)
The chapters in this section of this publication share a common denominator. From various perspectives, they deal with design education as transcending the narrow confines of a nascent design discipline. They support the notion that designerly ways of knowing require the synthesis of cognitive skills that have relevance to a wide spectrum of contexts. Thus, they represent a trend in the right direction and confirm the shift in the epistemology of design towards a wider social role for design. The chapters deal specifically with teaching and learning issues that enhance the role of design in this new context and reveal the concerns of the authors as educators to seek instructional ways that can support this shift.
Keywords: Design education; Cognitive skills; Employability; Interdisciplinarity; Life-long learning; Creativity